Peculiarities of the spindle ermine moth (Yponomeuta cagnagellus H?bn.) biology in the Kharkiv Forest-Park - Zinchenko, O. V. (Forestry and Forest Melioration, 2019)
Introduction Recently, the state of the environment has deteriorated. Thus, it is an urgent matter to study effective ways to protect suburban plantations against phytophagous insects which are characterized by the ability to reproduction outbreaks. Natural and man-made suburban plantations are very common in Kharkiv. However, the phytophagous species composition for certain forest species as well as the biology of the pests have not been thoroughly studied yet. One of the dangerous for suburban plantations pests is Yponomeuta cagnagellus (H?bn., 1810). Materials and Methods Field studies were conducted from 2017 to 2018 in Kharkiv Forest-Park. Laboratory tests were done in the Ukrainian Research Institute of Forestry and Forest Melioration named after G. M. Vysotsky. The plants Euonymus europaeus L. and E. verrucosus Scop. were the objects of the research. Results We found that Y. cagnagellus damages both species E. europaeus and E. verrucosus, but it prefers the latter. We confirmed that Y. cagnagellus passes the winter in the first instar larval state. In laboratory conditions, the larvae started feeding after 13 days after cut branches were brought into the room, which was at the same time with leaves opening. We recorded that larvae began forming a visually seen webby nest when a first completely open leaf appeared on a branch. In natural conditions, after wintering, Y. сagnagellus started feeding in late April-early May in 2017, and almost two weeks earlier – in 2018. On the 11th of May 2017 and the 2nd of May 2018 we could see the second instar larvae on the research plot. In 2017, the larvae’s development lasted 39 ± 5 days on average, in contrast to 2018, when it was 36 ± 5 days. Moths began flying on the 16th of June (in natural conditions) and on the 19th of June – in the laboratory conditions. The moths were flying for almost 2 months. The lifetime of the Y. сagnagellus moths without extra feeding made 19 ± 7 days on average. In laboratory conditions, the moth lifetime was more than two times higher with extra feeding with sugar syrup and lasted 48 ± 5 days. Females’ fertility was higher when they had extra nutrition. It made 167.4 ± 11.6 eggs. Conclusions After wintering the larvae begin feeding simultaneously with the first leaves and flower buds appearing. In natural conditions, the larvae’s development is 39 ± 5 days. In 2018, the Y. сagnagellus moths’ pupal stage began almost two weeks earlier compared to that in the previous research year. The mass flying of the moths takes place in the middle of June. In laboratory conditions, it was proved that the Y. сagnagellus moths’ lifetime and their females’ fertility increase when having additional feeding with sugar syrup. Taking into account that the territory of Left Bank Forest-Steppe of Ukraine represents ideal climatic conditions for the Y. сagnagellus moths’ development, it is necessary to thoroughly study the latter in order to timely forecast their mass reproduction outbreaks. 11 Figs., 3 Tables, 14 Refs.